Progress on bacteria promoting enterovirus infection and its mechanism - XU Chao; YANG Xiaolian; YUE Min; ZHU Shu (浙江大学学报. 农业与生命科学版)
Nowadays, coincided with more and more profound studies on intestinal microbiota, people are increasingly aware of its fundamental role in human and animal health. However, current studies mainly focused on nutritional metabolic disease, chronic and autoimmune diseases, little attention has been paid to its role in infectious diseases, particularly in viral diseases. Until very recently, researchers have begun to systematically study the interaction between intestinal bacteria and viruses. With the advance of relevant researches, the role of intestinal bacteria has been explored in viral invasion, pathogenicity and antiviral immunity; however, the mechanisms are largely unrevealed yet. Thus, in this article, we briefly reviewed recently highlighted advances in virus-bacteria interaction, especially elucidated relative mechanisms by which enteroviruses utilize bacteria to enhance viral invasion in vivo. In general, these mechanisms are segregated into two main categories: 1) direct facilitation of viral infection, including virion stabilization and enhancement of viral binding to host target cells; 2) indirect suppression of the antiviral immune responses in a manner of promoting in vivo replication. Discussion on mechanisms of enteroviruses exploiting intestinal bacteria for their invasion will be conducive to comprehensive understanding viral pathogenesis, elucidating virus-bacteria interactions and illuminating molecular mechanisms of enteroviruses evading host mucosal immunity. It can also provide novel insights and scientific basis into the development of novel enteroviral vaccines and associated adjuvants, as well as novel antiviral therapeutic approaches.